Effects of heat generation on airborne particles distribution in a hospital operating room - Ho, Woon Ping, 1993-, author 610434; Haslinda Mohamed Kamar, 1970-, supervisor 483836; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper